Censorship: Instagram (Turkey) - Voidly (Voidly Global Censorship Index, 2024)
CRITICAL severity censorship detected in Turkey. Data sourced from CensoredPlanet.
Censorship Incident ID: TR-2024-0002. Severity: critical. Confidence: 75%